2016
DOI: 10.1186/s13052-016-0217-z
|View full text |Cite
|
Sign up to set email alerts
|

Severe asthma features in children: a case–control online survey

Abstract: BackgroundVery few studies have explored the distinguishing features of severe asthma in childhood in Europe, and only one study was conducted in Southern Europe. The aim of this study was to provide a detailed characterization of children with severe asthma treated in specialized pediatric asthma centers across Italy.MethodsWe conducted a web-based data collection of family, environmental, clinical and laboratory characteristics of 41 patients aged 6–17 years with severe asthma, defined according to the recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
0
33
0
2
Order By: Relevance
“…persistent asthma are at higher risk than healthy children of worse QoL and behavioural problems, which are both related to asthma severity and symptom control [1][2][3] . In a previous study, we showed worse QoL in children and adolescents with severe asthma (SA) than in those with non-severe persistent asthma 4 . A reduced QoL has also been found in children with non-controlled asthma (NC) compared to children with well-controlled (WC) asthma 5,6 .…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…persistent asthma are at higher risk than healthy children of worse QoL and behavioural problems, which are both related to asthma severity and symptom control [1][2][3] . In a previous study, we showed worse QoL in children and adolescents with severe asthma (SA) than in those with non-severe persistent asthma 4 . A reduced QoL has also been found in children with non-controlled asthma (NC) compared to children with well-controlled (WC) asthma 5,6 .…”
mentioning
confidence: 84%
“…Sample size calculation and statistical analysis. The sample size for the two groups was determined on the basis of a previous study on asthmatic children 4 , where the PAQLQ score in SA was 5.9 (2.3-7.0) and 6.6 (3.7-7.0) in children with non-severe persistent asthma. Detecting the same difference with a 90% statistical power and a 5% significance level would have required a minimum sample size of 34 children for SA and 68 for MA.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, AR appears to be a negative earlylife predictive factor for an accelerated decline in lung function. Interestingly, a persistent, severe, and protracted history of AR is associated both with a major airway dysfunction and with a severe asthma phenotype [4,6].…”
Section: Rhinitis and Asthma: A Dog Biting Its Tailmentioning
confidence: 99%
“…These treatments offer an improvement in the management of the disease, but the heterogeneity of clinical outcomes and phenotypes suggests that many subjects could be difficult to treat and drugs could be not efficacious, especially in children (12-14). To face up this problem, the Society of Pediatric Respiratory Diseases (SIMRI) developed, for the first time in Italy, a registry for the collection of pediatric cases of SA with the aim to identify risks factors, clinical phenotypes and develop a customized therapy (15). Nevertheless, the SIMRI-registry results have two limitations: i) adolescents are not admitted to pediatric medical units and for this reason they are not recorded in the registry; ii) it is impossible to evaluate how the disease progresses and evolves from adolescence to adulthood.…”
Section: Introductionmentioning
confidence: 99%